2017
DOI: 10.21474/ijar01/4139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compensation and Job Insecurity on Employee Engagement (Study on Employee of Business Competition Supervisory Commission Secretariat).

Abstract: KPPU's Secretariat needs employees with high engagement rate to support it's duties and tasks. Employee with high engagement rate will try contribute positively to organizational performance. Employee Engagement can be affected by variables in the employee's workplace. This study aims to analyze the effect of Compensation and Job Insecurity on the Employee Engagement. Data that use in this research is primary data and secondary data. Sampling method used was convenient sampling. From a population of 329 employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
26

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 0 publications
1
26
0
26
Order By: Relevance
“…In Thus the ways the leader's behavior in directing followers will affect the employee's organizational commitment. Leadership has been researched by many previous researchers, including: (Riyanto, Pratomo, et al, 2017), and (Purba et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Thus the ways the leader's behavior in directing followers will affect the employee's organizational commitment. Leadership has been researched by many previous researchers, including: (Riyanto, Pratomo, et al, 2017), and (Purba et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Leadership styles have been studied by many previous researchers, including: (Riyanto, Pratomo, et al, 2017), (Purba et al, 2017).…”
Section: ) Cooperating With Subordinatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance has been examined by many previous researchers, including: (Ali, Limakrisna, et al, 2016), (Prihartono & Ali, 2020), (Ansori & Ali, 2017), (Harini et al, 2020), (Riyanto , Pratomo, et al, 2017), (Brata, Husani, Hapzi, 2017), (Agussalim, Kristin, et al, 2016), (Agussalim, Kristin, et al, 2016), (Ali, Limakrisna, et al, 2016), (Desfiandi et al, 2017), (Sulaeman et al, 2019), (Ansori & Ali, 2017), (Djojo & Ali, 2012), (Riyanto, Sutrisno, et al, 2017 ), (Prayetno & Ali, 2017), (Ridwan et al, 2020), (Djoko Setyo Widodo, P. Eddy Sanusi Silitonga, 2017), (Agussalim, Ayu Rezkiana Putri, et al, 2016), From several theories regarding performance, it can be concluded that performance is a result of work or the level of success achieved by workers in their field of work which can be directly reflected in the output produced both in terms of quantity and quality, according to the criteria applied to the job. Which can be measured through 1) technical ability; 2) Conceptual skills; 3) Responsibility; 4) Initiatives; and 5) Interpersonal relationship skills.…”
Section: Employee Performancementioning
confidence: 99%